DIGITAL MARKETING : KEGIATAN PEMASARAN ATAU PROMOSI BRAND PRODUK MELALUI INTERNET ATAU MEDIA SOSIAL - Nurjanah; Siti Wahyuningsih; Vivin Tri Nadya; Elmina Praptika Melati (JURNAL DAYA-MAS, 2023)
The development of the current era produces increasingly sophisticated facilities with the support of information technology, which can be used as a medium in developing customer satisfaction-oriented business ventures. Technology can not be denied has brought many changes in the dynamics of business competition today. Starting from the birth of new competitors, new product innovations, to the presence of various new business models. One form of technology integration is in marketing practices using digital marketing strategies. This form of digital marketing will be an alternative for small and medium enterprises (SMEs) with a limited promotional budget. The use of social media such as Facebook, Twitter, Instagram, and websites are alternatives that can be used to create brand awareness, engagement, sales and even loyalty. The integration of application-based digital marketing strategies in a business requires analysis of internal and external factors to determine the most effective digital marketing strategy. appropriate. This strategy is essentially a form of marketing that emphasizes brand communication to increase customer satisfaction. Theoretically, application-based digital marketing strategies can not only affect brand satisfaction, but can also lead to increased brand trust and brand loyalty.